2022
DOI: 10.1002/slct.202200182
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of BiVO4/RGO‐TNT Nanomaterials for Efficient and Recyclable Photocatalysis of Imidacloprid Insecticide

Abstract: The photocatalytic composites based on BiVO4, TiO2 nanotubes (TNT) and reduced graphene oxide (RGO) were synthesized by a one‐step hydrothermal synthesis method. The properties and structures of the samples were characterized by SEM, XRD, UV‐Vis DRS, Raman spectroscopy, photoluminescence spectroscopy and XPS. The effects of RGO‐TNT loading, pH, and dosage of catalysts on degradation efficiency were tested. The best removal results were occured on the condition that loading amount of RGO‐TNT was 10 %, solution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 59 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…During the process, superoxide and hydroxyl species are released, which play a crucial role in the photolytic destruction of pesticides [135]. In this regard, TiO 2 nanotubes/BiVO 4 /rGO photocatalyst has been hydrothermally prepared via a one-step strategy by Piao et al for the removal of imidacloprid insecticide [136]. They have shown that the dosage of ternary composite, pH, and loading amount of TiO 2 /rGO affects the degradation efficiency.…”
Section: Removal Of Pollutantsmentioning
confidence: 99%
“…During the process, superoxide and hydroxyl species are released, which play a crucial role in the photolytic destruction of pesticides [135]. In this regard, TiO 2 nanotubes/BiVO 4 /rGO photocatalyst has been hydrothermally prepared via a one-step strategy by Piao et al for the removal of imidacloprid insecticide [136]. They have shown that the dosage of ternary composite, pH, and loading amount of TiO 2 /rGO affects the degradation efficiency.…”
Section: Removal Of Pollutantsmentioning
confidence: 99%